Examining the Potential Usages, Features, and Challenges of Using ChatGPT Technology: A PRISMA-Based Systematic Review - Molla, Chanchal; Mani, Lisa; Bhuiyan, Mohammad Rakibul Islam; Hossain, Rashed (Migration Letters, 2023)
OpenAI developed ChatGPT, an AI-powered conversational agent platform that has the potential to revolutionize how people interact with technology. The study intends to determine the crucial features of ChatGPT in different sectors. Moreover, it identifies the prospective sectors of ChatGPT usage along with the challenges of using it in diverse areas. This study employs qualitative approaches, with a primary focus on utilizing secondary sources as the main data sources. Using PRISMA-based guidelines, this research applied specific keywords relevant to the primary objective of the inquiry, such as ChatGPT, characteristics, potential domains, and obstacles. Program developers, call centers, tourism education, digital marketing, mental health education, etc. have mainly benefited from utilizing ChatGPT from Bangladeshi perspectives. This study presents a set of standard features and challenges to gain a comprehensive understanding of the fundamental mechanism of utilizing ChatGPT.